Kekuatan Rasa Teh dan Tekstur Es Batu untuk Meningkatkan Strategi Penjualan Es Teh di Desa Tambak Rejo Waru Sidoarjo - Anisa Yulia Saputri; Devina Rizqy Firnanda; Misbachul Munir; Samuji Samuji (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Beverage business competition in the modern era is growing rapidly due to marketing developments and the many beverage and food brands that have become popular in the community. This makes business competition must develop its business to be more attractive. Indonesians not only drink mineral water, but also tea. The popularity of tea, encourages many beverage manufacturers to try to produce new products. Vina's iced tea makes iced tea with a combination of sweetened condensed milk, one of the popular types of tea. This study aims to analyze the effect of tea flavor intensity and ice cube texture on iced tea marketing strategies in Tambak Rejo Village, Waru, Sidoarjo. In the beverage industry, flavor and texture are important factors that influence brand image and product attractiveness in the market. This study uses qualitative and quantitative methods, to find out how consumers respond to the quality of the tea flavor they offer and the freshness of the ice cubes, and how these two factors affect the region. We are investigating how this can help increase sales of iced tea. This study shows that improving the unique taste of tea and the use of ice cubes with optimal texture can improve consumer experience, strengthen brand image, and influence purchasing decisions. Therefore, a strategy to improve product quality by considering aspects of taste and texture is the main key to increasing the competitiveness and sales of ice the village of tambak rejo. This article uses the Praticipatory learning and action (PLA) method or active field learning method is a participatory research method in which consumers and business actors are directly involved in the process of community service activities. In the context of iced tea sales strategies, the PLA method is used to understand how the intensity of tea flavor and texture of ice cubes affect consumer satisfaction and increase sales.